Analyzing SME's Data Visualization, Business Challenges, and Solutions: A Seven Stars Review - Elizade, Akkord (Jejaring Penelitian dan Pengabdian Masyarakat, 2024)
This comprehensive report encapsulates a thorough analysis conducted on the extensive Seven Stars dataset. Leveraging advanced data visualization techniques, the analysis has been meticulously executed to extract meaningful insights and elucidate intricate patterns within the dataset. By delving deep into the data, the report identifies a spectrum of potential business challenges that the organization may encounter, both in the present and future landscapes. These challenges encompass diverse realms such as market fluctuations, resource allocation, and operational inefficiencies. In response to the identified challenges, a robust set of solutions is proposed, tailored to address each issue methodically. Drawing upon best practices and industry expertise, these solutions aim to bolster the organization's resilience and competitiveness in the dynamic business environment. Moreover, to facilitate seamless data management and decision-making processes, a bespoke dashboard has been meticulously crafted. This intuitive dashboard serves as a centralized platform, enabling stakeholders to effortlessly manipulate and analyze data from disparate sources, thereby fostering informed decision-making and strategic planning. In essence, this paper serves as a comprehensive roadmap for the organization's data-driven journey, guiding it towards sustainable growth and success in an ever-evolving business landscape. Through diligent analysis, strategic foresight, and proactive problem-solving, the organization can chart a course towards long-term prosperity and resilience.